Exemplifying Values: Ma. Venkataram's Journey with RSS - Bhavya. P; Somashekar (PT FORMOSA CENDEKIA GLOBAL, 2024)
In the tapestry of Ma. Venkataram's life, his journey with the Rashtriya Swayamsevak Sangh (RSS) emerges as a vivid thread, woven with the fabric of unwavering values and steadfast dedication. As he walked the path of service and leadership within the RSS, Venkataram exemplified the very essence of integrity, compassion, and selflessness. From his earliest days as a member, Ma. Venkataram embraced the ethos of the RSS with zeal and commitment. Guided by the principles of self-discipline, social responsibility, and nation-building, he embarked on a journey of personal growth and collective upliftment. His steadfast dedication to the organization's mission, coupled with his innate humility and empathy, endeared him to his peers and mentors alike. As Ma. Venkataram rose through the ranks to become the Convener of South Karnataka for the RSS, he brought with him a wealth of experience and a profound sense of purpose. In this role, he served as a bridge-builder, fostering harmony and cooperation among diverse communities. His leadership was characterized by inclusivity, fairness, and a deep-seated commitment to the welfare of all